Dampak Kebijakan Pemerintah dalam Keberlanjutan PLTU Batang Terhadap Visi Indonesia 2024 Terkait Pengelolaan Lingkungan - Muhammad Zahiir Al Faraby (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The construction of the Batang Steam Power Plant (PLTU) has positive economic impacts but has the potential to harm the environment and local communities. The use of coal as PLTU fuel causes air and environmental pollution, posing a threat to ecosystem balance. The response to this challenge is evident through the issuance of Presidential Regulation 112/2022 by the Indonesian Government. This regulation strengthens the commitment to energy transition towards Net Zero Emission, aligning with the Vision of Indonesia 2045. With a focus on sustainability and well-being, Presidential Regulation 112/2022 emphasizes the prohibition of new PLTU constructions without affecting those already in operation, such as PLTU Batang. This step is expected to lead Indonesia towards environmentally friendly electricity development.